Analyzing the Impact of Trade Reforms on Welfare and Income Distribution Using CGE Framework: The Case of the Philippines - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 2003)
Tariff reform, particularly tariff reduction, is one of the major economic reforms implemented in the last one and half decades in the Philippines. The paper attempts to analyze the effects of the tariff reduction from 1994 to 2000 on household income and welfare using a computable general equilibrium (CGE) model calibrated to the 1994 social accounting matrix (SAM). Insights that can be drawn from the tariff reduction experiments include: (a) significant drop in domestic prices; (b) improvement in export competitiveness through the effective depreciation in the real exchange rate; (c) reallocation of production and resources towards the non-food manufacturing sector, which is a dominant sector both in trade and production; (d) drop in agriculture wages and increase in production wages; and (f) factor substitution favoring skilled production workers. The effects on nominal income are biased against rural households. This is largely because of the decline in agriculture wages and the improvement in production wages. However, the significant drop in prices, especially consumer prices, offsets almost all of these negative effects. As a result, both real household income and consumption improve. Therefore, the tariff reduction program is generally welfare-improving as indicated by the positive increase in the equivalent variation (EV) both for total and across households.
Keywords: 330; trade reforms; income distribution; computable general equilibrium (CGE); welfare; Handelsliberalisierung; Zollpolitik; Einkommensverteilung; Wohlfahrtsanalyse; Allgemeines Gleichgewicht; Philippinen; Verteilungswirkung; CGE-Modell